Early Sensory and Temperament Features in Infants Born to Mothers With Asthma: A Cross-Sectional Study - Mallise, Carly A.; Murphy, Vanessa E.; Campbell, Linda E.; Woolard, Alix J.; Whalen, Olivia M.; Milton, Gabrielle; Mattes, Joerg; Collison, Adam; Gibson, Peter G.; Karayanidis, Frini; Lane, Alison E. (Frontiers in Psychology, 2021)
Maternal asthma in pregnancy is associated with an increased risk of adverse perinatal outcomes. Adverse perinatal outcomes may result in poorer infant developmental outcomes, such as temperament and sensory difficulties. This study aimed to 1) assess differences in temperament and sensory features between infants born to mothers with and without asthma and 2) investigate differences in these infant behaviours as a function of maternal asthma severity and asthma control. Mothers completed the Carey Temperament Scales and the Sensory Profile 2 at either 6 weeks, 6 months or 12 months postpartum. Overall, we observed no significant differences between infants born to mothers with and without asthma in their temperament or sensory features; scores in both domains fell within the normative range. More infants in the asthma group, however, were reported to be highly distractible. When compared with normative data, infants in both groups were reported to have poor predictability of biological functions and fewer infants engaged in low levels of sensory behaviours. Some infants were observed to experience difficulties with hyper-reactivity within several domains. Maternal asthma severity and control during pregnancy was not linked to significant differences between infant temperament and sensory features. The present findings indicate that infants born to mothers with asthma are not at an increased risk overall for temperament or sensory difficulties, compared to control infants. However, a subset of infants may be at risk for attention or sensory hyper-reactivity difficulties. Further research into the developmental outcomes of infants born to mothers with asthma is warranted.